2019
DOI: 10.1590/s1808-185120191804225382
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diffusion-Weighted Mri of Patients With Spine Metastases

Abstract: Objective: The role of diffusion-weighted MRI in differential diagnostics and predicting the survival of patients with spine metastases was studied. Methods: The study included data from MRI and morphological studies of 23 patients with spine metastases. Results: The values obtained for the apparent diffusion coefficient (ADC) of tumors were compared with their histological type, cell density and Ki-67 proliferation index. The effect of ADC values on overall patient survival was also assessed. A reliable inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The extraosseous component typically follows usual hemangioma in all pulse sequences with high T1 and T2 signals as well as uniform post-contrast enhancement [9]. Methods of diffusion-weighted MRI with the construction of ADC maps enables visualization of restriction of diffusion of water molecules associated with proliferative activity and high cell density, which is typical for the tumor process, what enables the nature of the lesion to be differentiated [12]. Some studies show that the ADC value of vertebral hemangiomas is significantly higher than that of malignant lesions [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extraosseous component typically follows usual hemangioma in all pulse sequences with high T1 and T2 signals as well as uniform post-contrast enhancement [9]. Methods of diffusion-weighted MRI with the construction of ADC maps enables visualization of restriction of diffusion of water molecules associated with proliferative activity and high cell density, which is typical for the tumor process, what enables the nature of the lesion to be differentiated [12]. Some studies show that the ADC value of vertebral hemangiomas is significantly higher than that of malignant lesions [12].…”
Section: Discussionmentioning
confidence: 99%
“…Methods of diffusion-weighted MRI with the construction of ADC maps enables visualization of restriction of diffusion of water molecules associated with proliferative activity and high cell density, which is typical for the tumor process, what enables the nature of the lesion to be differentiated [12]. Some studies show that the ADC value of vertebral hemangiomas is significantly higher than that of malignant lesions [12]. A study performed by Geneidi et al demonstrated the diagnostic value of a restricted pattern by DWI for the discrimination between benign and malignant lesions, and the results showed that the best cut-off criterion is ADC of 0.67, and this means that 0.67 indicates malignant result while >0.67 is defined as benign results with a sensitivity of 94%, specificity of 79% and accuracy of 87% [13].…”
Section: Discussionmentioning
confidence: 99%